Effect of water and lipophilic alcohols or amines on the 4‐dodecylbenzenesulfonic acid‐catalyzed esterifications, trans‐esterifications, and amidations. Issue 9 (31st March 2017) - Wallis, Christopher; Cerny, Muriel; Lacroux, Eric; Mouloungui, Zephirin
Abstract : 4‐Dodecylbenzenesulfonic acid (DBSA) was employed in the esterification of oleic acid (OA) and the trans ‐esterification of oleic oil (OO) with 1‐butanol as alcohol in the presence of various degrees of excess water. Under these conditions DBSA was found to be a highly active esterification catalyst regardless of excess water content, but was found to be a less effective for trans ‐esterification reactions. Lipophilic alcohols of differing straight and branched C3‐6 chains were also tested on mixtures of OA/water (1:1) in DBSA‐catalyzed esterifications; OO/water (1:1) in trans ‐esterifications; and OA/OO/water (1:1:1) in simultaneous esterifications and trans ‐esterifications. While longer straight chain alcohols generally gave a two‐fold increase in yield of their corresponding alkyl oleates to 80%+, we observed a doubling from 30–50% to 60–95% of alkyl oleate yield for the OO/OA/water mixture. DBSA‐catalyzed amidations of OO and methyl oleate emulsions in water were conducted with 1‐butyl and 1‐heptyl amine where it was found that the more lipophilic the ester moiety the higher the yield of alkyl amide. Practical applications: The practical advantages of DBSA as catalyst are high conversions to the desired product along with its tolerance to high quantities of water, emulsified within the lipid material. A capacity to transform a range of substrates with varying lipophilic character in a range of condensation reactions. In addition, we demonstrate that esterification and trans ‐esterification reactions could be performed simultaneous and in the presence of high quantities of water. This is of direct interest to the transformation of waste sources of lipids that often contain a mixture of triglycerides and free fatty acids in various concentrations, emulsified with waste water. Furthermore, we demonstrate that all of the value‐added products/co‐products can be separated by an effective and industrially relevant methodology, including recovery of the DBSA catalyst as well as the water and water soluble co‐products, such as glycerol. A 4‐Dodecylbenzenesulfonic acid (DBSA) is demonstrated to be an effective polyvalent catalyst for the recovery of aqueous emulsified lipids by conversion into value‐added products. DBSA proved to be a polyvalent catalyst showing high activity using a range of substrates, performing esterification, trans ‐esterification, and amidations reactions efficiently despite the potential detrimental presence of high water loadings. The commercial incentive of our system is the phase separation of the product mixture into the converted lipids for use as biofuels and glycerol for resale as a fine chemical. Abstract : A 4‐Dodecylbenzenesulfonic acid (DBSA) is demonstrated to be an effective polyvalent catalyst for the recovery of aqueous emulsified lipids by conversion into value‐added products. DBSA proved to be a polyvalent catalyst showing high activity using a range of substrates, performing esterification, trans ‐esterification, and amidations reactions efficiently despite the potential detrimental presence of high water loadings. The commercial incentive of our system is the phase separation of the product mixture into the converted lipids for use as biofuels and glycerol for resale as a fine chemical.